Electrokinetic supercharging in nonaqueous capillary electrophoresis for online preconcentration and determination of tamoxifen and its metabolites in human plasma - Thang, L. Y. (Elsevier B.V., 2016)
An online preconcentration method, namely electrokinetic supercharging (EKS), was evaluated for the determination of tamoxifen and its metabolites in human plasma in nonaqueous capillary electrophoresis with ultraviolet detection (NACE-UV). This method was comprehensively optimized in terms of the leading electrolyte (LE) and terminating electrolyte (TE) injection lengths, as well as electrokinetic sample injection time. The optimized EKS conditions employed were as follows: hydrodynamic injection (HI) of 10 mM potassium chloride as LE at 150 mbar for 36 s (4% of total capillary volume). The sample was injected at 10 kV for 300 s, followed by HI of 10 mM pimozide as TE at 150 mbar for 36 s (4% of total capillary volume). Separation was performed in 7.5 mM deoxycholic acid sodium salt, 15 mM acetic acid and 1 mM 18-crown-6 in 100% methanol at +25 kV with UV detection at 205 nm. Under optimized conditions, the sensitivity was enhanced between 160- and 600-fold when compared with our previously developed method based on HI at 150 mbar for 12 s. The detection limit of the method for tamoxifen and its metabolites were 0.05–0.25 ng/mL, with RSDs between 2.1% and 3.5%. Recoveries in spiked human plasma were 95.6%–99.7%. A comparison was also made between the proposed EKS approach and the standard field-amplified sample injection (FASI) technique. EKS proved to be 3–5 times more sensitive than the FASI. The new EKS method was applied to the analysis of tamoxifen and its metabolites in plasma samples from breast cancer patients after liquid–liquid extraction.